THE INACTIVATION OF ENTEROVIRUS INFECTIVITY BY THE SULFHYDRYL REAGENT p-CHLOROMERCURIBENZOATE - Choppin, Purnell W. (The Rockefeller University Press, 1961)
The infectivity of several enteroviruses was inactivated by the sulfhydryl reagent p-chloromercuribenzoate (PCMB). The rate of inactivation was dependent on the ionic environment in which the reaction was carried out. Inactivation of infectivity was reversed by the thiol compound, reduced glutathione. Under certain conditions, PCMB prevented the adsorption of some enteroviruses to monolayer cultures of monkey kidney cells. The results suggest that enterovirus sulfhydryl groups are involved in the establishment of infection, and that they play a role in the adsorption of virus to host cells.